The world-system of academic capitalism: Process of consolidation of the entrepeneurial university Las Encuestas de Opinión en la Universidad Autónoma de Ciudad Juárez: ¿Un Caso de Exclusión del Profesorado? - César Silva Montes (Arizona State University, 2009)
This article presents an analysis of the system of the faculty evaluation by their students at the Universidad Autonoma de Ciudad Juarez (UACJ). The study was conducted following an interpretative and ethnographic methodology; empirical data was obtained based on participative observation. My presence on a daily basis allows me to register the processes in detail. In this methodology, the subjectivity, ideology and political stand of the researcher are made explicit. Results from the study indicate that for the perspective of the university administration, the faculty evaluation validates the teaching quality, and it is a referent to justify the professor exclusion from the university's incentive program. The faculty views the student evaluation as a control of their labor and as a revenge mechanism from those students who felt that will fail the course. The student perceives the evaluation as a mandatory and unimportant task, because its results do not modify the faculty pedagogic practice. Although there is an agreement between the administration and the faculty to maintain the student evaluation process for merit incentive purpose, faculty questions if this type of evaluation is appropriate for all the disciplines; the validity of peer evaluations; and, the student's judgment to leave them without labor economic incentives. As a result of the found divergence, it is proposed a dialogue among the professors; University's administration, and the students to generate an opinion poll in agreement to the context. En el presente artículo se analiza la encuesta de opinión que realiza el alumnado de la Universidad Autónoma de Ciudad Juárez (UACJ) para evaluar la docencia. Desde una metodología interpretativa y etnográfica, basada en la observación participante, se recopilaron los datos empíricos. Mi presencia permanente en la dinámica cotidiana, permitió registrar con detalle la aplicación de la encuesta. En esta metodología, la subjetividad, la postura política e ideológica del investigador son explícitas. Los hallazgos del estudio señalan que para la administración de la UACJ la encuesta es un aval de la calidad de la enseñanza y un referente para excluir al profesorado del programa de incentivos económicos. Según, el profesorado es una forma de control de su labor y de venganza del alumnado por la insatisfacción de la calificación obtenida. El estudiantado la concibe como una tarea obligatoria e intrascendente pues el profesorado no modifica su práctica pedagógica. Aunque existe acuerdo entre administración y profesorado de mantener la puntuación para recibir estímulos económicos, el último cuestiona sí los rubros de la encuesta aplican en todas las disciplinas, la necesidad de evaluar entre pares y el peso del estudiantado para dejarlos sin remuneraciones extras. Derivado de las divergencias encontradas, se plantea un diálogo entre profesorado y estudiantado con la administración para elaborar una encuesta de acuerdo al contexto de la institución.